Cover Image, Volume 35, Issue 2. Issue 2 (2nd February 2022) - Leow, Liang Joo; Teh, Natalie
Abstract : The cover image is based on the Short Report Clinical clearance of complex basal cell carcinoma in patients receiving sonidegib: A case series by Liang Joo Leow and Natalie Teh, https://doi.org/10.1111/dth.15217 .